Sistematización de la XXX versión del Festival Concurso Nacional de Danza Andina del municipio de Nemocón (2023)
This degree work has the purpose of analyzing in detail the organization and execution process of the XXX version of the National Andean Dance Competition Festival in the municipality of Nemocón, Cundinamarca. The research is based on a systematization of the event, taking as reference the experience of the researcher, who has actively participated in the cultural processes of the municipality during the last fifteen years, especially in the development of the festival as a teacher and manager.